Advances in open source hydroinformatics for flood modeling and disaster education - Gomes Junior, Marcus Nóbrega (2023)
Floods are one of the deadliest natural disasters and are affected by increased urbanization and climate change effects. Associated with floods are the pollutant transport and fate, reducing the water quality of rivers. The proper modeling of rainfall into runoff and the carrying of pollutants through overland flow depends on the scale of the time and space discretization of the watershed. To this end, one-dimensional (1D) or two-dimensional (2D) models are usually used to express the hydrodynamics. The objective of this work is to advance hydroinformatics of catchment-scale hydrology and hydrodynamics by the development of new computational tools adapted for flood and water quality problems, especially adapted to perform simulations in poorly gauged catchments although not limited to. By coupling a hydrologic model to a hydrodynamic model, it is possible to investigate effects such as estimating the impacts of unprecedented floods in vulnerable catchments or improving flood awareness through a serious gaming approach. This paper is divided into an introductory chapter 1, six research papers from Chapter 2 to Chapter 7, and the conclusions chapter. Chapter 2 shows an integrated hydrologic-hydrodynamic modeling framework used for real-time-control that accounts for catchment quasi-2D kinematic overland flow, lumped reservoir routing considering controllable orifices and weirs, and 1-D diffusive-like channel. Chapter 3 shows an innovative approach for 2D diffusive-like overland flow modeling (HydroPol2D), accounting for a more complete fully distributed hydrologic model (i.e., Green-Ampt infiltration and non-linear reservoir for stage-discharge overland flow modeling) coupled with evapotranspiration and groundwater recharge modeling. Chapter 4 presents a Global Optimization strategy to perform automatic calibration of HydroPol2D water quantity and quality parameters under single or multi-site, multi-event, observations. Chapter 5 enhances HydroPol2D by including a Human-Instability modeling capacity to estimate not only flood areas, but also risk of dragging due to the flood wave propagation in the 2D mesh grid. HydroPol2D is a 2D fully distributed model suitable for overland flow; therefore, some enhancements would be required to accurately simulate 1D unsteady flow when inertial terms of the shallow water equations are dominant. To this end, Chapters 6 and 7 develop a full momentum 1D solver suitable for regular and irregular cross-sections modeling with overbanks parametrized with different roughness coefficients. Chapter 6 develops the model (HydroHP) and Chapter 7 shows an application of 1D Dam-Break for 20 dams in Brazil, including the Brumadinho Dam. Finally, Chapter 8 shows the conclusions and future steps to continue the development of the models presented in this dissertation.